Compressional Pc 4 pulsations observed at synchronous orbit - Tonegawa, Yutaka (1982)
P(論文) Magnetic oscillations of Pc 4 type ULF waves in the period range from 40 to 180s are examined using the ATS-6 magnetometer data during the period from June 1 to August 31,1974. During this period the satellite was located at a magnetic latitude of 10°. It is found that there are two typical types of waves; compressional (meridionally polarized) and transverse (azimuthally polarized) waves. The transverse waves occur mainly in the early morning hours, while the compressional waves occur in the afternoon hours. The compressional waves exhibit rather shorter periods (40-110s) than the periods of the transverse waves (90-180s). The calculation of eigen mode period using the recent GEOS 2 plasma density data shows that the period of compressional waves agrees well with the calculated period of the second harmonic oscillation of the magnetic field line passing through the satellite. The compressional waves occur closely associated with ring current proton flux oscillations. A bounce resonant condition between azimuthally propagating waves and ring current protons is examined. The resonant condition is satisfied when the azimuthal angular wave number is longer than ∿100. It suggests that these compressional Pc 4 waves can not be observed on the ground due to the ionospheric screening effect. departmental bulletin paper